Age-Related and Pathogen-Specific Variations in C-Reactive Protein Levels Among Urinary Tract Infection Patients - Nnodim, Johnkennedy; Itunu, Adepoju Olorunfemi; Amarachi, Ikem Promise (Generasi Sains Indonesia, 2025)
This study evaluated serum C-reactive protein (CRP) levels among urinary tract infected patients attending Madonna University Teaching Hospital in order to determine inflammatory response patterns associated with urinary tract infections. A cross-sectional experimental design was employed involving 105 participants comprising 52 urinary tract infected patients and 53 apparently healthy controls. Serum CRP concentrations were measured using the Enzyme-Linked Immunosorbent Assay method, while statistical analysis was performed using SPSS version 26. The findings demonstrated that UTI patients exhibited significantly higher CRP concentrations compared to healthy controls. Age-related analysis further revealed elevated inflammatory responses among children and adolescents relative to adults. Comparative bacterial analysis showed that Escherichia coli infections produced the highest CRP levels, followed by Proteus mirabilis and Klebsiella pneumoniae. The novelty of this study lies in its integrated evaluation of age-dependent and pathogen-specific inflammatory responses among UTI patients within a Nigerian tertiary healthcare setting. The findings provide important evidence supporting the clinical relevance of CRP as a rapid biomarker for assessing inflammatory severity and host-pathogen interactions in urinary tract infections. The study further contributes to improving biomarker-based infection assessment and inflammatory monitoring in resource-limited clinical environments.